A Preliminary Study with Qualitative Diatom Tests - Yorulmaz, Coşkun; Arıcan, Nadir; Arslan, Hıdır; Afacan, İlyas; Çetin, Gürsel; Fincancı, Şebnem Korur (The Bulletin of Legal Medicine, 1999)
In cases of suspected drowning, especially if the deceased recovered from water displays an advanced stage of putrefaction, quantitative and qualitative diatom tests are the only diagnostic tools. In recent years, quantitative diatom analysis has been increasingly applied in Turkey. In this study, we attempted to perform additional! qualitative test together with comparative analysis oF water specimens obtained From the scene of death with the aim to eliminate the doubt about diatom examination. For this purpose, we carried out a qualitative and quantitative diatom analysis in a total of 13 cases (6 in fresh and 7 in salt water) referred to the Council of Forensic Medicine For medicolegal autopsy. Diatom analysis was also performed in water specimens obtained from the scene during investigation. We also investigated 7 further cases of suspected drowning in three different artificial small lakes. In these cases, no water specimens were available. We evaluated diatom of the tissues of these 7 cases both quantitatively and qualitatively considering that each case who was drown in the same lake may be accepted as a control of each other. Based on our results, concomitant qualitative cliatom analysis with quantitative tests are more releavent than quantitative diatom investigations alone.Key words: Drowning, autopsy, diatom.
Keywords: drowning; autopsy; diatom